SPOTKANIA MIĘDZYKULTUROWE Z PERSPEKTYWY ORGANIZATORA – CIENIE I BLASKI - Kic-Drgas, Joanna (Neofilolog, 2018)
Intercultural meetings are present in foreign language teaching and they are currently gaining popularity. It is the result not only of globalisation but also of the increasing sensitivity and awareness of the coexistence of different cultures. The advantages of intercultural meetings have been appreciated by teachers and tutors working with different age groups. Leaving aside their benefits, they constitute an enormous organisational challenge at the same time. The following paper aims at discussing the opportunities and potential difficulties related to intercultural challenges based on the survey conducted among Polish and German teachers organising intercultural exchanges.